2003
DOI: 10.1046/j.1439-0523.2003.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analysis of Solanum phureja DNA introgressed into potato dihaploids

Abstract: Introgression of Solanum phureja DNA into S. tuberosum dihaploids was analysed by the use of amplified fragment length polymorphism (AFLP) markers. Five dihaploids, derived from crosses between S. tuberosum cv. Pentland Crown and two different S. phureja pollinators (IVP48 and EC90) were investigated by use of 17 AFLP primer pairs. Also 30 dihaploids, derived from pollination of five different S. tuberosum seed parents with S. phureja IVP101, were investigated for the presence of S. phureja‐specific markers. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(31 reference statements)
1
14
1
Order By: Relevance
“…SNP markers specific for the S. phureja inducers occurred in almost all genotypes and on nearly all of the potato chromosomes (Table S1 ). These results are in contrast to those of Straadt and Rasmussen ( 2003 ), who observed no introgression of pollinator DNA in 30 haploid genotypes derived from crosses with S. phureja IVP101 using AFLP markers for their introgression analysis but also indicated that the introgression rate may be influenced by the tetraploid S. tuberosum seed parent. Rarely, more than a single introgression marker could be detected on the same chromosomes in the P208 population, but more often in the P809 population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…SNP markers specific for the S. phureja inducers occurred in almost all genotypes and on nearly all of the potato chromosomes (Table S1 ). These results are in contrast to those of Straadt and Rasmussen ( 2003 ), who observed no introgression of pollinator DNA in 30 haploid genotypes derived from crosses with S. phureja IVP101 using AFLP markers for their introgression analysis but also indicated that the introgression rate may be influenced by the tetraploid S. tuberosum seed parent. Rarely, more than a single introgression marker could be detected on the same chromosomes in the P208 population, but more often in the P809 population.…”
Section: Discussioncontrasting
confidence: 99%
“…Clulow et al ( 1991 ) suggested that S. phureja chromosomes are eliminated from embryonic cells during cell divisions after the fertilization of egg cells, resulting in haploid progeny. This finding was also reported in later introgression analyses (Clulow and Rousselle-Bourgeois, 1997 ; Straadt and Rasmussen, 2003 ; Ercolano et al, 2004 ). Haploid populations derived by parthenogenesis have been used for genetic analyses (Kotch et al, 1992 ) and to identify markers that are linked to nematode resistance (Pineda et al, 1993 ); however, the number of genotypes used in the RFLP mapping approach was very small with 37 haploid individuals.…”
Section: Introductionsupporting
confidence: 79%
“…In potato, evidence in support of parthenogenesis has been reported (Wangenheim et al 1960;Montelongo-Escobedo and Rowe 1969;Peloquin et al 1996) . At the same time, genome elimination is supported by the detection of genetic markers from the haploid inducer in euploids and aneuploids arising from haploid induction crosses (Clulow et al 1991(Clulow et al , 1993Waugh et al 1992;Wilkinson et al 1995;Allainguillaume et al 1997;Clulow and Rousselle-Bourgeois 1997;Straadt and Rasmussen 2003;Ercolano et al 2004) . Whole genome sequencing provides a more informative and reliable method to assess the genetic contribution of the haploid inducer.…”
Section: Genetic Contribution From Haploid Inducer Not Detected Despimentioning
confidence: 99%
“…This alternative hypothesis is supported by the presence of inducer-specific AFLP, RFLP, or isozyme markers in presumably dihaploid progeny. Often, progeny exhibiting genetic markers from the haploid inducer are also aneuploid, suggesting inheritance of an entire chromosome from the haploid inducer (Clulow et al 1991(Clulow et al , 1993Waugh et al 1992;Wilkinson et al 1995;Allainguillaume et al 1997;Clulow and Rousselle-Bourgeois 1997;Straadt and Rasmussen 2003;Ercolano et al 2004) . These results are consistent with haploid induction crosses in maize (Riera-Lizarazu et al 1996;Zhao et al 2013) , Arabidopsis (Maheshwari et al 2015;Tan et al 2015;Kuppu et al 2015) , and oat-maize hybrids (Riera-Lizarazu et al 1996) in which one or more haploid inducer chromosomes persist in otherwise haploid plants.…”
Section: Introductionmentioning
confidence: 99%
“…The AFLP technique (Vos et al 1995) generally produces between 50 and 100 scorable fragments per polimerase chain reaction (PCR) reaction (Maughan et al 1996). This technique has been widely used in various crops, including cultivated potatoes (Powell et al 1996;Milbourne et al 1997;McGregor et al 2000;Avrova et al 2002;Straadt and Rasmussen, 2003;Furini and Wunder, 2004) and their wild relatives (Kardolus et al 1998). In the last years, the AFLP technology was used to differentiate genotypes used as ancestors in potato genetic improvement programs.…”
mentioning
confidence: 99%